Goal orientations and performance: role of temporal norms - Lee, Cynthia; Hui, Chun; Tinsley, Catherine H; Niu, Xiongying (Journal of International Business Studies, 2006)
We tested the relationships between Chinese employees' goal orientation and their performance, as well as the moderating effects of temporal norms (future planning and scheduling) on this relationship. Results from employees across seven different organizations in China demonstrated that the mastery goal orientation was positively related to job performance. The performance goal orientation was unrelated to employment outcomes. Further, results showed that a mastery goal orientation was most useful when future planning was emphasized and scheduling was de-emphasized.